Repair of large osteochondritis dissecans lesions using a novel multilayered tissue engineered construct in an equine athlete. (20th May 2016) - Stack, J. David; Levingstone, Tanya J.; Lalor, William; Sanders, Ruth; Kearney, Clodagh; O'Brien, Fergal J.; David, Florent
Abstract: Osteochondral lesions resulting from osteochondritis dissecans are problematic to treat and present a significant challenge for clinicians. The aims of this study were to investigate the use of a scaffold‐assisted microfracture approach, employing a novel, multilayered, collagen‐based, osteochondral graft substitute in the treatment of severe osteochondritis dissecans of both lateral femoral trochlear ridges in an equine athlete, and to assess the potential of this novel scaffold to enhance repair of the osteochondral unit. A 15 month‐old female filly presented with large osteochondritis dissecans lesions involving both femoral lateral trochlear ridges. After routine arthroscopic debridement and microfracture of the subchondral bone, multilayered osteochondral defect repair scaffolds were implanted into the fragmentation beds in both left and right femoropatellar joints via mini‐arthrotomies. Exploratory arthroscopy 5 months postimplantation revealed smooth cartilaginous repair tissue, contiguous with the adjacent cartilage, covering the defect. At 22‐month follow up, the filly had no signs of lameness and was exercising at her intended level. Radiographically, although still slightly flattened, the femoral trochlear ridges were smooth, with no evidence of osteoarthritis. Ultrasonographically, the defects were filled with bone and covered with an overlying cartilaginous layer, with the trochlear ridge contour almost entirely restored. This report demonstrates the effective clinical use of this novel, multilayered, osteochondral defect repair scaffold in the treatment of osteochondritis dissecans of an equine athlete. The successful repair achieved here using this novel scaffold in an equine patient with large bilateral lesions shows the potential for clinical translation in the treatment of human patients presenting with osteochondral defects. Copyright © 2016 John Wiley & Sons, Ltd.